HYGIENE PERSONAL MAHASISWA PADA MATA KULIAH PASTRY DI WORKSHOP TATA BOGA JURUSAN KESEJAHTERAAN KELUARGA FT UNP - Sari, Novita; Elida, Elida; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research aims to get an overview of personal hygiene at Pastry courses. This type of research is a research survey, the population is students who follow the Pastry courses listed on the semester January-June 2015 that took the Pastry Courses and sample taken through the total sampling. Research instrument using the format of research using using two alternative answers. Data analysis techniques by means of determining frequency distribution data and determine the level of attainment of respondents. Personal hygiene in workshops the Home Economic is good. Personal hygiene with sub indicators of fingers and hands well.Indicators of the head and the hair well. Indicators of clothing work clothes very well. Indicators shoes stated very good . Keywords: Personal Hygiene, Pastry Courses, Workshops